Cognitive styles and academic performance of students in library and information science - Gonzales, Grace Marie B. (2001)
This study looks into the cognitive styles of undergraduate students of the UP Institute of Library Science to find out if: 1) there is a predominant cognitive style and style combination among them; 2) the student's gender, age, year level and mode of entry affect his or her cognitive style; and 3) the students' cognitive styles and/or style combinations affect their performances in LIS core courses as indicated by their final grades.